Comparison of feetme insoles with a motion capture system coupled to force plates for assessing gait and posture - Piao Huang; Andrey Mostovov; Raphaël Cohen; Céline Cadilhac; Raphaël Pionnier (Scientific Reports)
Abstract Traditional gait measurement systems are often limited by factors such as cost, complexity, prolonged setup times, and requirements for specialized training and expertise. Wearable pressure- and motion-sensing insoles have opened new possibilities for accessible gait analysis in real-life conditions. This study evaluated the equivalence of FeetMe insole measurements of gait parameters to those of a laboratory gold standard, optoelectronic motion capture system coupled to force platforms (MoCap/FP). Gait and posture parameters were assessed in 37 healthy adults by FeetMe insoles and by MoCap/FP system simultaneously. Means and variances were compared, and inter-device agreement was assessed for each parameter. Between-device equivalence was demonstrated for all parameters assessed (two one-sided t tests: P < .001). For static parameters, six of 13 variables presented excellent interclass correlation coefficients (ICCs ≥ 0.90) and three had good ICCs (≥ 0.75 to < 0.90). Moreover, 10 of 11 spatiotemporal parameters showed excellent accuracy (ICCs ≥ 0.90), and three of four kinetic parameters showed moderate-to-good accuracy (ICCs between 0.78 and 0.89). In summary, FeetMe can be considered as a valid gait measurement tool compared to the high precision MoCap/FP system and could be used in clinical practice to assess a wide range of gait and posture parameters, overcoming some limitations of traditional systems.